The Impact of A Stock Split and the Economic Value Added on Stock Return - Simon Grima; Surtikanti Surtikanti; Sri Dewi Anggadini (International Business and Accounting Research Journal, 2020)
The purpose of this study is to analyse the impact before and after the stocks split on stock return and analyze the impact of the economic value added (EVA) on the stock return of financial service sector companies listed on the Indonesia Stock Exchange (IDX) who carried out a stock split between the period 2014-2019. To do this we used event studies and tested the information content of the market reaction of an announcement. We sampled 35 financial statements from a population of 250 financial statements of companies conducting a stock split listed on the Indonesia Stock Exchange and analyzed the data using simple Linear regression. We also tested whether there was a deviation of assumptions from test normality and autocorrelation. The results showed that no significant differences and negative stock returns before and after the stock split. And there is a significant and positive effect partially between the economic value added on returns